Calculating the cost for employee turnover in the IT industry in Macedonia by using a web calculator - Mitrovska Sanja; Eftimov, Lјupcho (Comenius University in Bratislava, 2016)
The little meaning, which HR managers attach to managing the rate of employee turnover, is mostly cause by the lack of specific tools to calculate its impact on the profitability of the companies. This paper presents a universal calculator for calculating the cost of employee turnover, which can be used in developing various effective retention strategies. More precisely, the research focuses on the expense of turnover rate in the IT industry in the Republic of Macedonia, calculated using a web calculator specifically designed for this purpose. This web calculator can be used to compute the cost of employee turnover in any industry, with appropriate minor modifications and adjustments of its elements.
Keywords: employee turnover, IT industry, costs calculation, web calculator, Macedonia